2021
DOI: 10.1590/1981-5271v45.4-20210066.ing
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric assessment of the Instructional Materials Motivation Survey (IMMS) instrument in a remote learning environment

Abstract: Introduction: Motivation contributes greatly to learning, being a predictor of student performance. Thus, instruments that assess motivation after exposure to different teaching strategies and materials can contribute to the analysis and decision on its effectiveness. In this sense, the Instructional Materials Motivation Survey (IMMS) instrument measures students’ motivation after instructional activities. Objective: This study aimed to evaluate the evidence of validity of the IMMS, previously translated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…This instrument has been endorsed and used in a multitude of investigations, some of them closely related to this project [57,60,61]. All of these authors concluded that the IMMS must be adapted to the characteristics of the students and the instructional program of each investigation.…”
Section: Methodology and Instrumentsmentioning
confidence: 99%
“…This instrument has been endorsed and used in a multitude of investigations, some of them closely related to this project [57,60,61]. All of these authors concluded that the IMMS must be adapted to the characteristics of the students and the instructional program of each investigation.…”
Section: Methodology and Instrumentsmentioning
confidence: 99%
“…Subsequently, its psychometric validation generated the IMMS version validated in Brazil (IMMS-BRV), consisting of 25 items divided into four dimensions: Interest, Confidence, Attention, and Expectation (Online Resource 1 ). The internal consistency reliability, measured by Cronbach’s alpha coefficient, for the complete IMMS-BRV instrument, is 0.95, being 0.93 for the Interest dimension, 0.87 for the Confidence dimension, 0.76 for the Attention dimension and 0.78 for the Expectation dimension [ 35 , 36 ]. Its purpose is to measure the respondent’s motivation using the Likert scale, with the following score: (1) I totally disagree; (2) I partially disagree; (3) I neither disagree nor agree; (4) I partially agree; and (5) I totally agree.…”
Section: Methodsmentioning
confidence: 99%
“…While originally formulated for face-to-face teaching, the ARCS model and its accompanying instrument have found utility in various instructional contexts involving technology-mediated training, such as virtual teaching with video, podcasts, MOOCs, computer-assisted teaching, distance learning, interactive video, computer animations, and simulations [45][46][47][48][49][50][51]. Recently, it has been increasingly employed in training actions involving immersive reality (IR) [3,[52][53][54][55].…”
Section: Motivation As a Key Element For Learning And Trainingmentioning
confidence: 99%